Evaluation of resources in the study of industrial and culinary properties for the varietal characterization of rice (Oryza sativa L.) - Farco, Andrea Paola (2021)
Fil: Farco, Andrea Paola. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.